Effects of heating rate on upper thermal limit: insights from cardiac performance and transcriptomic response in mudflat snail Batillaria attramentaria - Du, Li-Na; Du, Ying-Hui; Han, Guo-Dong (Frontiers in Marine Science, 2024)
Studying the effect of heating rate on upper thermal limit has gained considerable attention in enhancing our mechanistic understanding of how organisms respond to changing temperatures in the context of climate change. The present study aimed to investigate the effects of heating rate on upper thermal limit and understand the physiological and molecular mechanisms used by organisms to cope with thermal stress at different heating rates. Batillaria attramentaria snails were exposed to slow (3°C/h) or fast (9°C/h) heating rates. The median lethal temperature (LT50) of snails exposed to these varying heating rates was determined. Additionally, we assessed heart rate under constant heating and investigated the transcriptomic response at the temperature where the heart rate reaches zero (FLT). The results revealed that snails exhibit a higher upper thermal limit (approximately 1.5°C) during fast heating as compared to slow heating. On average, the heart rate of slowly heated snails was 11 beats per minute lower than that of fast heated snails when the temperature was below 45°C. The findings indicate that the metabolic rate is lower during slow heating compared to fast heating when subjected to the same level of thermal stress. When exposed to a temperature of FLT, snails initiated a typical heat shock response to thermal stress, which included the increased expression of genes encoding heat shock proteins (HSPs) and protein disulfide isomerase (PDIA5) involved in protein folding. Remarkably, the genes glucose-regulated protein 94 (GRP94) and Calnexin, which are associated with the binding of unfolded proteins, showed distinct up-regulation in snails that were heated slowly, indicating the accumulation of misfolded proteins. The accumulation of misfolded proteins, coupled with additional energy consumption, may contribute to the lower upper thermal limit observed at a slow heating rate. Our research provides valuable insights for determining the realistic upper limits of temperature tolerance and improving predictions of how organisms will be affected by climate change in the future.